2019
DOI: 10.1016/j.rmed.2018.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Airway wall thickening on CT: Relation to smoking status and severity of COPD

Abstract: Airway wall thickening in cigarette smokers is thought to be a result of inflammatory changes and airway remodeling. This study investigates if CT-derived airway wall thickening associates to disease severity in smokers with and without COPD and if airway wall thickening is reversible by smoking cessation. We examined 2000 smokers and 46 never-smokers who returned for a 5-year follow-up visit in the COPDGene-study. Multivariable regression analyses were performed at visit 1 to associate airway wall thickness (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 21 publications
2
47
0
1
Order By: Relevance
“…A study investigating whether the airwall thickening derived from CT is associated to diseases in smokers with or without COPD, showed that the Pi10, which was calculated from extracted airways and expressed as the square root of wall area of a hypothetical airway with internal perimeter of 10 mm, was increased in all GOLD stages and associated with worse FEV 1 predicted. Besides Pi10 was significantly higher in current smokers compared to former smokers and the average Pi10 of never smokers was significantly lower than both former and current smokers (45). In this study 2000 smokers and 46 never smokers group were from the COPD Gene study and were followed up for 5 years so they had repetitive CT scans.…”
Section: Imaging Modalitiesmentioning
confidence: 86%
“…A study investigating whether the airwall thickening derived from CT is associated to diseases in smokers with or without COPD, showed that the Pi10, which was calculated from extracted airways and expressed as the square root of wall area of a hypothetical airway with internal perimeter of 10 mm, was increased in all GOLD stages and associated with worse FEV 1 predicted. Besides Pi10 was significantly higher in current smokers compared to former smokers and the average Pi10 of never smokers was significantly lower than both former and current smokers (45). In this study 2000 smokers and 46 never smokers group were from the COPD Gene study and were followed up for 5 years so they had repetitive CT scans.…”
Section: Imaging Modalitiesmentioning
confidence: 86%
“…Given that airway parameters on chest CT have been regarded as radiological biomarkers for COPD and associated with air ow obstruction in all GOLD stages (35)(36)(37), airway structure and airway parameters on chest CT were obtained automatically to assess airway remodeling in our study. We demonstrated that the COPD group showed apparent changes in the airway structure, characterized by the thickened bronchial wall and rough and curved bronchial lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Emphysema score was calculated by calculating the percentage of lung voxels below −950 HU after resampling the CT images to 3 mm slice thickness, normalization, and bullae analysis ( Gevenois et al, 1996 ; Gallardo-Estrella et al, 2016 ). Pi10 is the square root of the airway wall area for a theoretical 10 mm lumen perimeter airway derived using the linear regression of the square root of segmented wall area against the lumen perimeter ( Charbonnier et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%